تقدير الذات والسلوك العدواني لدى حالات من تلاميذ ضحايا التنمر دراسة حالة - بمتوسطة ابن هاني الاندلسي - - جرار سيرين; غضبان بلقيس; اشراف: خرخاش اسماء (جامعة محمد بوضياف -المسيلة, 2025)
باستعمال منهج دراسة الحالة واستعمال كل من المقابلة النصف موجهة والملاحظة الموجهة ومقاييس لفحص مؤشرات الدراسة على حالتين متمدرستين بمتوسطة ابن هاني الاندلسي بالموسم الدراسي 2023-2024، حيث تم استعمال مقياس الوقوع ضحية تنمر و مقياس تقدير الذات لروسن بيرج. وأيضامقياس السلوك العدواني للأطفال لأمال عبد السميع مليجي باضة. حيث خلصت النتائج لتشابه نتائج الحالتين ووجود بعض الاختلافات في المسار الدراسي والظروف الصحية بينما تشابهت نتائج الفرضيات حيث: - مستوى التنمر لدى حالتين ضحايا التنمر المدروسة كبيرة وهذه النتيجة توافقت مع الفرض المقدم في الدراسة. بينما باقي النتائج فقط جاءت معاكسة تماما لفروض الدراسة حيث: - مستوى تقدير الذات لدى الحالتين ضحايا التنمر المدروسة مرتفع. - مستوى العدواني الجسدي لدى ضحايا التنمر المدروسة منخفضة. - مستوى العدواني اللفظي لدى ضحايا التنمر المدروسة منخفضة. - مستوى العدائية لدى حالات ضحايا التنمر المدروسة منخفضة. قد يرجع تباين نتائج الدراسة مع معظم الفروض المقدمة كون المرحلة العمرية التي تم دراستها جد حرجة وتتشاكل مع مشارف دخول مرحلة المراهقة ونهاية مرحلة الكمون،أيضا العديد من العوامل المحيطة كالمعاملة الوالدية والتعامل مع الأقران والنظام التربوي المتبع في المؤسسات التعليمية. ملخص الدراسة: بالانجلزية: Abstract Utilizing a case study methodology, this research employed semi-structured interviews, guided observations, and standardized measures to examine study indicators in two middle school students at Ibn Haney Al-Andalusi Middle School during the 2023-2024 academic year. The study utilized the Victimization of Bullying Scale and Rosenberg's Self-Esteem Scale, as well as Amel Abdel SamadMilyejiBadawi's Child Aggression Scale. The findings revealed similarities between the two cases, with some differences in academic trajectories and health conditions. However, the results of the hypotheses were consistent, indicating that: The level of bullying experienced by the two studied victims of bullying was high, which aligns with the hypothesis presented in the study. Conversely, the remaining results contradicted the study's hypotheses, demonstrating that: The level of self-esteem among the two studied victims of bullying was high. The level of physical aggression among the studied victims of bullying was low. The level of verbal aggression among the studied victims of bullying was low. The level of hostility among the studied victims of bullying was low. The discrepancies between the study's findings and most of the hypotheses presented may be attributed to the critical age group studied, which coincides with the transition to adolescence and the end of the latency stage. Additionally, numerous environmental factors, such as parental treatment, peer interactions, and the educational system implemented in educational institutions, may have contributed to these discrepancies. Keys Words: Studied Victims Of Bullying, Self-Esteem, Physical Aggression, Verbal Aggression, Hostility.